ANALYSIS OF THE INFLUENCE OF RETURN ON ASSET (ROA), RETURN ON EQUITY (ROE), DEBT TO EQUITY RATIO (DER) AND TOTAL ASSET TURN OVER (TATO) ON STOCK RETURNS IN TELECOMMUNICATIONS SUB-SECTOR COMPANIES LISTED ON THE BEI - Awalia, Shafira; Nurulrahmatiah, Nafisah (JURNAL DIMENSI, 2024)
Stock returns are one of investors' considerations in making investment decisions. Company stock returns are determined by the high demand and supply price of shares in the capital market. One of the factors that influences stock returns in a company is the company's financial performance. The aim of this research is to determine the effect of Return On Equity (ROA), Return On Equity (ROE), Debt to Equity Ratio (DER) and Total Asset Turn Over (TATO) on share returns in Telecommunications Sub-Sector Companies listed on the BEI. The instrument used in this research is a list of tables in the form of financial reports consisting of balance sheet data in the form of total assets, total debt, total capital. As well as a profit and loss report consisting of total sales, net profit and share price of Telecommunications Sub-Sector Companies listed on the Indonesian Stock Exchange (BEI). The population in this research is all telecommunications companies registered on the IDX, namely 22 companies. The sample in this research was 7 telecommunications companies listed on the IDX from 2017-2022. The sampling technique used is purposive sampling. Research data was collected by means of documentation and literature study and then analyzed by hypothesis testing, t test and f test. The research results show that Return On Assets (ROA), Return On Equity (ROE), Debt to Equity Ratio (DER) and Total Asset Turn Over (TATO) simultaneously have a significant effect on stock returns in telecommunications sector companies listed on the IDX.